STRATEGI NAFKAH DAN KESEJAHTERAAN KELUARGA PADA KELUARGA PETANI TADAH HUJAN - Sugiharto, Adam; Hartoyo, Hartoyo; Muflikhati, Istiqlaliyah (Department of Family and Consumer Sciences, Faculty of Human Ecology, IPB University, 2016)
Creating several livelihood strategies by families is an effect of limitation faced by families. This study aimed to analyze livelihood strategies and their effects on the welfare of non-irrigated farm families in Playen District of Gunung Kidul Regency. Region that is used as a location of study was an area which was far from the capital of district and nearby area of the capital of district. The study involved 100 families interviewed using a questionnaire. Data were analyzed using descriptive analysis and binary logistic regression. Based on indicator of family welfare level from BKKBN, the study found that the prosperous family is as much as 57.0 percent and the rest is not prosperous. Overall, the study found that majority of farmer family has mix livelihood strategies. The results showed that the age of husband which is younger, the increase of spending cost per capita, and the increase of physical capital of a family directly affect the welfare of the family. On the other hand, the kind of coping strategies of farmer family and also the location of the family does not affect the family welfare. These results indicate the absence of the influence of coping strategies towards family welfare of non-irrigated farm family in this study.